Diarrhea Risk Factors of Toddlers in Jember District, 2022 - Aini, Annisa Fitrah; Ariyanto, Yunus; Noveyani, Adistha Eka (Preventia: The Indonesian Journal of Public Health, 2025)
Diarrhea is a disease characterized by passing feces three or more times a day. The occurrence of diarrhea is also influenced by sociodemographic factors (nutritional status) and environmental factors (access to clean water, access to sanitary latrines, and living in flood-prone areas). The purpose of this research focuses on finding risk factors for diarrhea and mapping the risk factors of diarrhea. This study used an ecological study design, in which the population is all sub-districts in Jember. Secondary data were used in this research. The data were analyzed using statistical correlation analysis using SPSS and mapping using GIS software. The statistical analysis results between each risk factor and the incidence of diarrhea indicated that all the risk factors were correlated with diarrhea. Maps showed that each sub-district has different potential risk factors. Our recommendation is determining specific programs to be implemented in each area, considering potential risk factors.